Ontario 10 Applied (MFM2P)
topic badge
Expand perfect squares

Interactive practice questions

Complete the proof that $\left(a+b\right)^2=a^2+2ab+b^2$(a+b)2=a2+2ab+b2.

$\left(a+b\right)^2$(a+b)2 $=$= $\left(\editable{}\right)\left(\editable{}\right)$()()
$=$= $a\left(\editable{}\right)+b\left(\editable{}\right)$a()+b()
$=$= $\editable{}+\editable{}+\editable{}+\editable{}$+++
$=$= $\editable{}+\editable{}+\editable{}$++
Approx 2 minutes
Sign up to try all questions

Complete the proof that $\left(a-b\right)^2=a^2-2ab+b^2$(ab)2=a22ab+b2.


Consider the following expressions.



Expand and simplify second-degree polynomial expressions involving one variable that consist of the product of two binomials [e.g., (2x + 3)(x + 4)] or the square of a binomial [e.g., (x + 3)^2], using a variety of tools and strategies

What is Mathspace

About Mathspace